Dunlop's Sosiological System Approach: Application at a Leading Manufacturing Industry in Bangladesh - Khan, Anisur Rahman; Islam, Md. Zohurul (Universitas Negeri Surabaya, 2022)
This is the first-ever study that applies John Dunlop’s seminal sociological theoretical approach to the industrial relations system to analyze the working environment in Walton–a hi-Tech leading manufacturing plant in Bangladesh. Starting its operation in 1977 as a small-scale enterprise, Walton currently captures a big portion of the domestic market and also extending its operation to international markets. The study is based on the five testable components of industrial relations including government/actor, technology, ideology, market and power. Questionnaires were developed to collect data from 120 respondents from different departments of the company through random sampling. The results confirm that the Dunlop approach works in a befitting manner in most cases. The findings bear important lessons for practitioners and researchers using theoretical tools of system approach in the sphere of employee relations.